Océan Austral, Iles de Kerguelen / d'après les travaux plus récents . Service hydrographique de la marine . 1937 - France. Service hydrographique de la marine (1963)
Décembre 1961 edition no. 3. Corr. . 1963 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in purple.; Includes sheet coverage key "Index des mouillages" and 5 coastal views: Vue A. Ilot du Rendez-vous -- Vue B. Entrée de la Baie de l'Oiseau -- Vue C. Mont Campbell -- Vue D. Nord des Iles Kent -- Vue E. Entrée de la Baie du Hopeful Grayscale; 1:250,000